HUBUNGAN TINGKAT PENDIDIKAN IBU DAN PEMBERIAN ASI EKSKLUSIF DENGAN KEJADIAN STUNTING PADA BALITA DI PUSKESMAS SUNGAI LEKOP KOTA BATAM - Kurnia, Heppy; Utami, Risqi (Universitas Batam, 2020)
Stunting is impaired growth and development that children experience from a number of impacting factors with poor nutrition being one of them. Children are defined as stunted if their height-for-age is more than two standard deviations below the WHO Child Growth Standards median. According to the report of the Health Office of Batam in 2018, out of 20 puskesmas (community clinics) in the region, five of them recorded the highest prevalence of stunting among toddlers with Puskesmas Sei Lekop being the highest hitting 110 reported cases (0.89%). This research aims to discover the correlations between motherâ€™s educational background and exclusive breastfeeding practice on the toddlerhood stunting prevalence in Puskesmas Sei Lekop, Batam, in 2019.The research design employs analytic method with cross-sectional approach. Conducted from April to August 2019, the research involves 97 respondents in total. The data analyzing technique employs chi-square. The findings reveal the correlations between motherâ€™s educational background and the stunting prevalence among toddlers with Ï-value 0.01 < 0.05; and between exclusive breastfeeding practice and the stunting prevalence among toddlers with Ï-value 0.00 < 0.05. In conclusion, the findings confirm the correlations between motherâ€™s educational background and exclusive breastfeeding practice on the stunting prevalence among toddlers. In suggestion, the following researchers who are interested in studying similar subject are expected to develop more detailed parametric variables and investigate other possible factors that may contribute or are related to stunting issues.